Evaluation and Modification of the Physical Therapist Clinical Performance Instrument. Issue 2 (18th June 2021) - Wolden, Mitch; Drevyn, Elsa; Flom-Meland, Cindy; Gusman, Lori N.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Doctor of Physical Therapy (DPT) programs and clinical instructors (CIs) must have a reliable and valid instrument to assess the clinical competence of each DPT student. The Physical Therapist Clinical Performance Instrument (PT CPI) is the most commonly used instrument to assess DPT students' clinical competence. Validation studies of the PT CPI: Version 1997 and Version 2006 have identified 3 factors that account for students' clinical performance. Given the widespread use of the PT CPI and CIs and DPT programs concerns, evaluation of the current PT CPI (PT CPI: Web) as a three-factor model is warranted. The purpose of our investigation was to evaluate the three-factor model, suggest model modifications, and then analyze the modified PT CPI model. Methods: PT CPI data were analyzed from 703 DPT students' clinical experiences from 3 institutions. Data analyses were conducted in 2 phases. Phase 1: Confirmatory factor analysis (CFA) was conducted for the three-factor PT CPI (model I). Phase 2: CFA was performed on the modified PT CPI (model II). The 2 models were then compared to determine the preferred model. Results: The proposed 2-factor PT CPI (model II) with 15 performance criteria was found to be the preferred model over the current three-factor PT CPI (model I) for measuring DPT students learning and performance during clinical experiences. Discussion and Conclusion: Modifying the current three-factor PT CPI (model I) to the proposed 2-factor model (model II) may better support DPT students, CIs, and DPT programs in the assessment of DPT students' clinical learning and performance. Our findings also provide preliminary evidence to decrease the length of the PT CPI while maintaining instrument integrity.